2008
DOI: 10.1261/rna.718708
|View full text |Cite
|
Sign up to set email alerts
|

General, rapid, and transcription-dependent fragmentation of nucleolar antigens in S. cerevisiae mRNA export mutants

Abstract: In the yeast Saccharomyces cerevisiae, mutation of some effectors of mRNA nuclear export leads to the rapid accumulation of HSP104 RNA in transcription site-associated foci. We have screened the S. cerevisiae complement of viable gene deletion mutants for their inability to export HSP104 RNA. The 15 strains identified comprise deletions of components of the THO, Thp1p/Sac3p, and nuclear pore complexes. In all three mutant classes, retained RNA overlaps the HSP104 transcription site. Thus, an early block to HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Nup59p is required for mRNA export after severe heat shock but is dispensable for peripheral localization of INO1 after inositol starvation (Thomsen et al 2008;Ahmed et al 2010;Light et al 2010). We found that a nup59D had no defect in stress-responsive transcriptional memory at TSA2, unlike nup42D cells ( Figure 5); a similar result was found for the related nup60D mutant (Thomsen et al 2008) (not shown). This strongly argues against a general defect in mRNA export as the cause of the transcriptional difference.…”
Section: Nuclear Pore Component Nup42p Is Required For the Faster Gensupporting
confidence: 81%
“…Nup59p is required for mRNA export after severe heat shock but is dispensable for peripheral localization of INO1 after inositol starvation (Thomsen et al 2008;Ahmed et al 2010;Light et al 2010). We found that a nup59D had no defect in stress-responsive transcriptional memory at TSA2, unlike nup42D cells ( Figure 5); a similar result was found for the related nup60D mutant (Thomsen et al 2008) (not shown). This strongly argues against a general defect in mRNA export as the cause of the transcriptional difference.…”
Section: Nuclear Pore Component Nup42p Is Required For the Faster Gensupporting
confidence: 81%
“…Further studies are required to resolve the identity of the polyA( ĂŸ ) RNA accumulating in the nucleolar aggregates, as polyA( ĂŸ ) RNA may represent either nascent mRNA exported via the CRM1 route or RNA destined for degradation by polyA( ĂŸ ) tag. However, the finding that ubiquitin is rate limiting for the aggregate formation suggests that ubiquitin-mediated licensing is required for RNA surveillance and export also in mammalian cells, as previously described in yeast (Thomsen et al, 2008;Houseley and Tollervey, 2009).…”
Section: Nucleolar Aggregates L Latonen Et Almentioning
confidence: 53%
“…We also speculate that some miRNAs could combine with target messenger RNAs in the nucleolus to be exported as ''presuppressed'' mRNAs, a somatic cell analogy with masked maternal mRNAs in oocytes. Consistent with this idea, there is evidence that the nucleolus is involved in mRNA nucleocytoplasmic transport (Schneiter et al 1995;Thomsen et al 2008), and some mRNAs have been shown to associate with the nucleolus (John et al 1977;Bond and Wold 1993;BĂĄrtovĂĄ et al 2008;Kim et al 2009). …”
Section: Discussionmentioning
confidence: 80%